Electrodeposition of alkali group I metals from room temperature ionic liquids - Wibowo, R (2011)
The work presented in this thesis involves the utility of room temperature ionic liquids (RTILs) as solvents in electrodeposition of Alkali Group I metals (excluding Fr). The first two chapters present fundamentals of electrochemistry which is the basis of this work followed by an overview of RTILs and a brief introduction to X-ray photoelectron spectroscopy. The results of five original studies are then presented as follows: • The deposition and stripping of Li/Li+ couple in several RTILs is studied in detail on Pt and Ni microelectrodes and the results are simulated using a mathematical model developed by the Compton Group • The study is then continued for Na/Na+ in several ionic liquids on a Ni microelectrode and the results are compared to that of Li/Li+ couple • The remaining members down the Group (K/K+, Rb/Rb+ and Cs/Cs+) are studied in ionic liquid N-butyl-N-methyl-pyrrolidinium bis(trifluoromethylsulfonyl)imide ([C4mpyrr][NTf2]) on a Ni microelectrode allowing comparison of electrode potentials throughout Group in the IL to be deduced. • The novel development of in situ electrochemical-X-ray photoelectron spectroscopy for monitoring the potassium deposition is reported • Electrochemical-XPS is used for monitoring rubidium deposition in competition with RTIL solvent breakdown The results presented show that several RTILs are able to support the electrodeposition of Alkali Group I metals due to their wide electrochemical windows and electrochemical stability. The simulation of the results allows thermodynamic and kinetic parameters such as the electrochemical rate constant (k0), diffusion coefficient (D), and formal potential (Ef0) and transfer coefficient (α) to be extracted. The trend in electrode potentials of the Group in [C4mpyrr][NTf2] is also presented and compared to that of in other solvents. The near zero vapour pressure property of the RTILs is also exploited for the development of in situ electrochemical-XPS; a new branch of spectroelectrochemistry.